2020
DOI: 10.1002/ana.25780
|View full text |Cite
|
Sign up to set email alerts
|

TRPV4 Antagonism Prevents Mechanically Induced Myotonia

Abstract: Objective Myotonia is caused by involuntary firing of skeletal muscle action potentials and causes debilitating stiffness. Current treatments are insufficiently efficacious and associated with side effects. Myotonia can be triggered by voluntary movement (electrically induced myotonia) or percussion (mechanically induced myotonia). Whether distinct molecular mechanisms underlie these triggers is unknown. Our goal was to identify ion channels involved in mechanically induced myotonia and to evaluate block of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…A second TRPV4 KO mouse line ( Fig. S1 B ) was generated by the Jackson Laboratory and previously characterized by our laboratory ( 42 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A second TRPV4 KO mouse line ( Fig. S1 B ) was generated by the Jackson Laboratory and previously characterized by our laboratory ( 42 ).…”
Section: Methodsmentioning
confidence: 99%
“…To determine whether endogenous TRPV4 protein is ubiquitinated in cells and whole tissue, we assessed an immortalized rat sensory neuron cell line (50B11 cells), the Madin-Darby canine kidney (MDCK) epithelial cell line, and mouse choroid plexus tissue; all of which express robust levels of TRPV4 (32,38,39). To immunopurify endogenous TRPV4, we used an anti-TRPV4 antibody that detects TRPV4 protein in cultured primary choroid plexus epithelial cells (40), kidney, and choroid plexus derived from wild type (WT), but not Trpv4 null mice (40)(41)(42) (Supplementary Fig 1A-B). Using this antibody, we achieved robust TRPV4 immunoprecipitation with little background compare to whole cell lysate inputs (Supplementary Fig.…”
Section: Trpv4 Is Mono-/multi-ubiquitinated In Multiple Cell Typesmentioning
confidence: 99%
“…Besides peripheral neuropathies, a very recent study elegantly showed that skeletal muscle TRPV4 channels are involved in mechanically induced myotonia because the latter is inhibited by TRPV4 inhibitors or missing in muscles of TRPV4 −/− mice [ 157 ]. The authors proposed that mechanical stimulation of muscle fibers induces the opening of TRPV4 channels, leading to sarcolemma depolarization that is normally dampened by ClC-1 chloride currents.…”
Section: Calcium Channel-related Myopathiesmentioning
confidence: 99%
“…The authors proposed that mechanical stimulation of muscle fibers induces the opening of TRPV4 channels, leading to sarcolemma depolarization that is normally dampened by ClC-1 chloride currents. In myotonic muscles, the defective ClC-1 chloride channel cannot counteract the TRPV4-induced depolarization that, in turn, triggers hyperexcitability [ 157 ].…”
Section: Calcium Channel-related Myopathiesmentioning
confidence: 99%
“…Based on studies of sustained depolarizations (sometimes termed plateau potentials) in neurons, a family of ion channels that might contribute is the transient receptor potential (TRP) ion channel family (Yan et al, 2009;Phelan et al, 2012). Members of the TRP ion channel family are expressed in skeletal muscle (Brinkmeier, 2011;Gailly, 2012), and we recently found that activation of TRPV4 plays a role in triggering percussion myotonia (Dupont et al, 2020).…”
Section: Rapid Transition Between Hyperexcitability and Inexcitabilitmentioning
confidence: 99%